PROBLEMS OF THE DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN THE RUSSIAN FEDERATION - Vladimir B. Zotov; K. N. Bazian (Статистика и экономика)
Public-private partnership (PPP) is a complex mechanism, which includes a variety of industry legislation, which together form a system of legislative regulation of relations at the interaction of private and public parties in the realization of long-term capital-intensive investment projects for the development of public infrastructure. The article describes the current state of PPP in the Russian Federation, the analysis of the main problems and needs integrated action (regulatory, institutional and investment) to improve and develop this project.